OFR-42-77 Fabricate And Evaluate Protective Canopies For 3-Foot Coal Seams - Wesley Hermanson (The National Institute for Occupational Safety and Health (NIOSH), 1976)
Canopies were designed, fabricated, installed, and demonstrated for mining machinery in 3-foot coal seams. A Wilcox PJ20 Auger miner, a Wilcox Bolter, a bee Norse 245 miner, and an Elkhorn Scoop AR3 modified to AR4 were fitted with canopies. The Wilcox Bolter canopy was hydraulically adjustable in height; the rest were manually pin adjustable. The machine operators' comments were adverse in each case. Restriction of visibility and body constriction into unaccustowed and tiring attitude were major objections, causing increased hazards and fatigue. Recommendations are made that roll bar protection be furnished in place of canopies for 3-foot seams to provide partial protection by deflecting and supporting roof falls but not covering the head of the operator. In this way, the effect on visibility would be minimized and fatigue from body restriction would not be increased.